2009
DOI: 10.2174/1874920800902010025
|View full text |Cite
|
Sign up to set email alerts
|

Factors that Affect Commitment to Continue Studies Among Business Students: A Comparative Study of Asian and Canadian Students studying in Canada

Abstract: This paper examines the effects of transformational leadership and of stress on students' commitment to continue their college or university studies. Asian and Canadian students enrolled in business management program at colleges and universities in British Columbia, Canada were surveyed to gauge their perceptions as to whether transformational leadership used by faculty members and stress affect their commitment to continue studies. The results suggest that when instructors implement transformational leadersh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…According to Anghelache (2013), the awareness level of the learner, the personality of the learner and the learners' performance affect the commitment of learners. According to Gill et al (2009), transformational leadership and learner stress have been identified as factors that influence learners' commitment. According to Jovi et al (2017), the usefulness of e-learning, ease of use and content design emphasize the significance of effective online learning methods.…”
Section: Impact Of Learners' Satisfaction On Learners' Commitment To Online Learningmentioning
confidence: 99%
“…According to Anghelache (2013), the awareness level of the learner, the personality of the learner and the learners' performance affect the commitment of learners. According to Gill et al (2009), transformational leadership and learner stress have been identified as factors that influence learners' commitment. According to Jovi et al (2017), the usefulness of e-learning, ease of use and content design emphasize the significance of effective online learning methods.…”
Section: Impact Of Learners' Satisfaction On Learners' Commitment To Online Learningmentioning
confidence: 99%
“…Practicing effective listening skills (e.g., showing students that you want to listen, being patient, holding your temper, going easy on argument and criticism, and asking relevant questions) can go a long way toward demonstrating respect and concern for students' personal feelings as well as overcoming communication and cultural barriers. Ultimately, instructors/professors should act as mentors (e.g., educate, advise, coach, support, and encourage) to students to fully overcome "the degree to which TL needs to be implemented" barriers [35].…”
Section: Implementing Transformational Leader-ship Behaviorsmentioning
confidence: 99%
“…In practice, although it may be difficult for some instructors/professors to increase their use of these TL behaviors and some students may eye a change in teaching styles with skepticism, the potential benefits far outweigh the costs, and such behaviors are develop-able. The importance of such a leadership development process, however, must be championed and strongly supported by senior leadership (e.g., the dean) [35].…”
Section: Implementing Transformational Leader-ship Behaviorsmentioning
confidence: 99%
“…Similarly, Lavy & Sand (2015) investigated understanding the gender differences in teacher-student interaction and found it gender-biased as that the majority of male instructors are inclined to intermingle more with males than with female students and also give them more opportunities to participate in class discussion. Gill et al (2011) elucidated that the students always consider their teachers an important pillar and great source of knowledge for every stage of academic life. Hence, teachers' teaching styles affect students both unfavorably and insistently in building their basic thinking abilities, they set up positive associations with their colleagues, lower staff, and with their institution administration.…”
Section: Introductionmentioning
confidence: 99%